Extroversion, Motivation and Language Learning: A Study of a Successful Language Learner - Qays Al Qaisi, Mohammed; Al_Jubori, Shahlaa Salih (International Journal of Psychosocial Rehabilitation, 2020)
Learning a new language has always been a tough task for students learning the language for academic purposes, or for social interactions in daily life. Students make a lot of effort to understand the language of the place they are living in to avoid alienation from the society. They use different strategies to improve their L2. These strategies include affective strategies, such as dealing with anxiety, encouraging oneself and rewarding. Getting into constant contact with native speakers is also one of the most essential ways learners use to develop their language fluency. (Green, Oxford 264).